Risk management in engineering and construction : tools and techniques - Ogunlana, Stephen O., 1957-; Dey, Prasanta (Spon research., 2020)
Today's businesses are driven by customer pull' and technological push'. To remain competitive in this dynamic business world, engineering and construction organizations are constantly innovating with new technology tools and techniques to improve process performance in their projects. Their management challenge is to save time, reduce cost and increase quality and operational efficiency. Risk management has recently evolved as an effective method of managing both projects and operations. Risk is inherent in any project, as managers need to plan projects with minimal knowledge and information, but its management helps managers to become proactive rather than reactive. Hence, it not only increases the chance of project achievement, but also helps ensure better performance throughout its operations phase. Various qualitative and quantitative tools are researched extensively by academics and routinely deployed by practitioners for managing risk. These have tremendous potential for wider applications. Yet the current literature on both the theory and practice of risk management is widely scattered. Most of the books emphasize risk management theory but lack practical demonstrations and give little guidance on the application of those theories. This book showcases a number of effective applications of risk management tools and techniques across product and service life in a way useful for practitioners, graduate students and researchers. It also provides an in-depth understanding of the principles of risk management in engineering and construction.